(untitled) (Quaderni di Gargnano, 2020)
The essay focuses on the political theme in Aragonese poetry between the reign of Ferrante and that of Federico. Through the analysis of the poems by some of the greatest court poets – from Perleoni to De Jennaro and Sannazaro – the author intends to demonstrate that political poetry is not a mere display of courtly flattery, but instead it contains precise doctrinal elements that contribute to strengthening the image of sovereigns and the monarchical ideology itself. Il saggio inquadra la tematica politica della poesia aragonese tra il regno di Ferrante e quello di Federico. Attraverso l’analisi della produzione di alcuni tra i maggiori poeti di corte – dal Perleoni al De Jennaro al Sannazaro – si mira a dimostrare che la poesia politica non è una semplice dimostrazione di adulazione cortigiana, ma contiene precisi elementi dottrinali che contribuiscono a rafforzare l’immagine dei sovrani e la stessa ideologia monarchica.